Sistema de monitoramento para auxílio de captura de morcego na região amazônica - LIMA, Tiago Nunes (2023)
The work aims to develop a data capture support system in the Epidemiology and Geoprocessing Laboratory (EpiGeo) of the Federal University of Pará (UFPA), with the objective of verifying the presence of viruses in the Amazon region. For the construction of the system the Arduino UNO microcontroller with some ultrasonic sensors makes the model HC-SR04 and the GSM / GPRS SIM900 Protector for sending text message to the laboratory researchers. In addition, in hardware, a software was developed in Java, with a MySQL database to control the information generated in the field activities and data storage through the microcontroller.